The impact of Holland’s political proposal in Brazilian literature (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
Radical Behaviorism was and continues to be criticized as a social-control philosophy, reactionary and anti-democratic. Holland replied to these criticisms emphasized the political role of behavior analysis on a commitment focused on social transformation, in which the countercontrol would have central role. Given the persistence of social and political criticism, this article aims to analyze the impact of Holland political proposal in Brazilian literature specialized in behavior analysis. A bibliographical survey was performed in 437 articles from three current active journals specialized in behavior analysis. The data obtained showed that Holland’s proposals did not have significant repercussion. The author is quoted in only 1.83% of total publications. The mention of countercontrol was also not significant (2.28%), suggesting that it is not a central concept to the discussions in the field.
Keywords: Holland; countercontrol; politics